2019
DOI: 10.1002/rsa.20854
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap percolation with inhibition

Abstract: We study a variant of the classical bootstrap percolation process on Erdős Rényi random graphs. The graphs we consider have inhibitory vertices obstructing the diffusion of activity and excitatory vertices facilitating it. We study both a synchronous and an asynchronous version of the process. Both begin with a small initial set of active vertices, and the activation spreads to all vertices for which the number of excitatory active neighbors exceeds the number of inhibitory active neighbors by a certain amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This difference is analogous to (Koulakov, Hromádka, & Zador, ) and (Roxin et al, ) on the single neuron level. With respect to the emergence of normal NBs, it has been shown in a model of asynchronous spike transmission in random networks that normally distributed NBs with small standard deviation occur if inhibition is strong enough to stop the spread of activity (Einarsson, Lengler, Panagiotou, Mousset, & Steger, ), consistent with the observation that inhibition dominates during NBs in vitro (Hájos et al, ). Further, supporting normally distributed NB size, the distribution of SPW amplitude has been observed to follow a truncated normal distribution (where the truncation stems from the SPW detection threshold) (see Sullivan et al, ), however, the relation between SPW amplitude and NB size is not clear.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This difference is analogous to (Koulakov, Hromádka, & Zador, ) and (Roxin et al, ) on the single neuron level. With respect to the emergence of normal NBs, it has been shown in a model of asynchronous spike transmission in random networks that normally distributed NBs with small standard deviation occur if inhibition is strong enough to stop the spread of activity (Einarsson, Lengler, Panagiotou, Mousset, & Steger, ), consistent with the observation that inhibition dominates during NBs in vitro (Hájos et al, ). Further, supporting normally distributed NB size, the distribution of SPW amplitude has been observed to follow a truncated normal distribution (where the truncation stems from the SPW detection threshold) (see Sullivan et al, ), however, the relation between SPW amplitude and NB size is not clear.…”
Section: Discussionmentioning
confidence: 53%
“…Our model investigates synchronous spike transmission propagated over one synaptic layer. Synchronous spike transmission over multiple layers has been studied in the context of synfire‐chains (Abeles, ) where it has been shown that in the absence of homeostatic plasticity the activity diverges quickly (Weissenberger, Meier, Lengler, Einarsson, & Steger, ) and the distribution of activity is very broad (Einarsson et al, ). Such divergence is consistent with our work: the tail of the input distribution is amplified over one synaptic layer and iterative amplification over multiple layers results in explosions of activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…some vertices are vaccinated or have a higher threshold for infection. See for example [18] for some recent work in this vein.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that for a range of the parameters, the process percolates on the combined graph but not on the random graph G n,p without local edges. In [16] the authors considered bootstrap percolation process on G n,p with vertices of two different types.…”
Section: Introductionmentioning
confidence: 99%